TRADISI BERARAK DARI RUMAH SIEMPU KE LAPANGAN TEMPAT SHALAT IDUL FITRI - Amanan Amanan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The Berarrak (parade) tradition from Siempu house to the Idul Fitri Praying place, the district of Gunung Sahilan, Kampar Regency, Riau is still exist and being practiced by the society of Kebundurian. This tradition is conducted to glorify leaders of custom, religion or government. The people of Kebundurian call it Tungku Tigo Sajorang. The purpose of this tradition also to show us that all the leaders work and live in harmony and based on the rule. There is also a good relationship between leaders and people. As a result of a good relationships, the development in this village will reach the goal as all people expected.